Risk Assessment of Financial Statements using the CFEBT Model - Lenka STRAKOVA; Pavol DURANA (Communications of International Proceedings, 2020)
This article discusses about risk assessment of financial statements using the CFEBT model and its modification. The financial statements of the entity serve as an information base for both external and internal users. Their function is to give a true and fair view of the financial position, performance and changes in the financial position of the entity. It is the effort to present the accounting entity in a more favorable image that leads the company's management to artificially improve the achieved financial results. This paper captures the development of profit or loss and cash flow, as well as the mismatch of accounting items in the entity's financial statements for a period of six years. Based on the CFEBT model and the modified CFEBT model, it is possible to assess whether deviations in the achieved values pose a risk of manipulation of financial statements beyond the scope of legislative rules. In the paper we use the analysis of selected models in order to evaluate the ability of users to detect the risk arising from the manipulation of financial statements beyond the true and fair view of accounting.
Keywords: Financial Statement; CFEBT Model; Creative Accounting; Financial Manipulation.